UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MAPEL PJOK MATERI SEPAK BOLA MELALUI METODE DEMONSTRASI DI KELAS V SD NEGERI 91 KENDARI TAHUN PELAJARAN 2021/2022 - Ahmad Anto (CV. ADIBA AISHA AMIRA, 2023)
The achievement of the results of observation and evaluation of PJOK lessons for CLASS V students in semester 1 of the 2021/2022 academic year is still below the minimum completeness criteria (KKM) set by the school, which is 70. Learning achievement data is shown by the grades of 25 students whose grades meet the KKM or above the KKM there are 7 students or 28% and 18 students or 72% who are under the KKM. Looking at the data on learning outcomes and the implementation of these subjects, it is very necessary for the learning process to improve its quality. In order for students' understanding of PJOK lessons to increase and learning objectives can be achieved optimally. So the researcher wants to use the demonstration method. This research is a class action research (classroom action research). This research was conducted at SD Negeri 91 Kendari Class V SD Negeri 91 Kendari. in semester 1, from October to December 2021. the research subjects were Class V students with a total of 25 students. Data collection methods in this study are observation, documentation and interview methods. The results of cycle I and evaluation can be seen that there is an increase in student learning outcomes, namely there are still 6 students who score less than 70 or students who complete 76% and the average student score is 77.4. Cycle II is a continuation of the previous cycle to establish and achieve research objectives. Lessons are delivered about soccer, the movement of kicking the ball with the inside of the foot, the outside of the foot and the instep, the movement of dribbling, the movement of sending the ball is delivered with a planned strategy as cycle I and learning activities are carried out more optimally. The results of cycle II showed an increase in student learning outcomes, namely the average value of 86 students, students who studied thoroughly reached 100% and 0 students who scored below the mark of completeness. From the results of research in cycle II, the researchers reviewed carefully that the demonstration method can improve student learning outcomes in the subject matter of soccer in class V SD Negeri 91 Kendari in the 2021/2022 academic year.